53.1k views
1 vote
3t + 5sqrt(t) - 2 = 0 solve by using substitution

User Bogdan D
by
4.4k points

2 Answers

4 votes
This is something that I haven’t learned yet but I think the answer is 25
User Christian Fredh
by
6.2k points
1 vote

Answer:

The answer is t=1/9

Explanation:

If we substitute sqrt(t) = u, then we can write the equation as 3u^2+5u-2=0.

Using the quadratic formula, we can solve that u = 1/3 and u = -2.

We can go back to our original substitution and say that sqrt(t) = 1/3. The sqrt(t) can not be -2 because a square root can not be negative.

If we solve the equation sqrt(t) = 1/3, we get that t=1/9.

User Insumity
by
4.9k points